Study of the Relationship between Sports Efficiency Index and the Classification Performance of the Clubs of the Brazilian Championship Series A - Hein, Adriana Kroenke; Hein, Nelson; da Rosa, Maycon Peter; Junior, Roberto Pires Soares; Siqueira da Silva, Fabio do Nascimento; Franco, Gabriel Ferreira (International Journal of Advanced Engineering Research and Science, 2021)
The performance of soccer clubs in Brazil has shown a significant evolution in the last decade. Considering the competitiveness of the market, there is a need to act as companies using sustainable management models. In fact, the purpose of sports institutions is to obtain titles and good results that allow them to generate greater revenues and make expenses and investments in search of perpetuity and ascension of objectives. In this sense, this survey compared the Sports Efficiency Indexes with the soccer clubs' Classification Performance, in the classification tables of the Brazilian Championship in the years 2017 and 2018. In order to meet the objective, data wrapping analysis (DEA) and Kendall's correlation coefficient were applied for evaluate investment performance. The results showed that in the period analyzed there was significant parity ration in part of the results found, since many clubs reached a position in the corresponding tournament with the ranking of sports efficiency. Then, it concluded that the better is the sporting efficiency team, the better its ranking in the championship. Searching for an efficient allocation of resources, the research seeks to contribute attesting to the need for a detailed examination of expenses and investments in the perspective of better results.